Assessment of Ecosystem Services and Disservices in Urban Environment Using Multispectral Image Analysis and Geospatial Mapping - Haque, Md Nazmul; Alam, Irtija; Rahman, Atif Aninda (MIST International Journal of Science and Technology, 2021)
Ecosystem service and disservice components have a great impact on the environment as well as on urban life. The aim of the research is to assess the impact of ecosystem services and disservices by tracking the change over a span of 15 years (2005-2020) using satellite image analysis. It was conducted in wards 23 and 29 of Khulna City Corporation (KCC), an area adjacent to the river. The overall work breakdown has been rounded up in a methodological framework which cleaved into two parts focusing on ecosystem services, disservices and multispectral image analysis steps. Multispectral image analysis has been done using Normalized Difference Vegetation Index (NDVI) and Normalized Difference Build-up Index (NDBI). On the other hand, geospatial analysis has been done using Digital Elevation Model (DEM), Service Area Analysis (SAV) and other mapping tool including Geographic Information System (GIS) to show the changed impact of both ecosystem components. The study areas attain provisioning, habitat, cultural and regulatory service components and the disservice elements have been sorted out according to sources. Comparative study showed increase in the buildup area; vegetation coverage because of increasing vegetation, cultivation and gardening practices; good weather and water circulation condition and water body conservation which has significant positive impact on the area. The disservice component like poor drainage condition and solid waste management system and risky infrastructures have negative impact, need to address for the betterment of residence and environment. MIJST, Vol. 09, June 2021 (55-65)